Particularizing the universal. Medievalist constructions of cultural and religious difference in Crusader Kings II - Kyyrö Jere (Bloomsbury Academic, 2025)
This chapter analyses the representations of culture and religion in Crusader Kings II, a digital game developed by the Swedish developer Paradox Development Studio and published by Paradox Interactive. The main focus is on the ways in which the game system (including the game rules, graphical representation and naming of game concepts) works to produce an effect and a feel of particular cultures and religions in a medieval setting, and how digital games should be approached as cultural products. Special attention is paid to representations of Northern Europe.
The central argument is that through a process of ‘particularisation’, which is at some points superficial, apparently different cultures and religions are represented as fundamentally similar. This type of particularisation not only results from the programming paradigm the game engine builds on, but especially from the cultural presuppositions and metamedievalist conceptions held by the game designers, which lead to quite different areas and populations being moulded to follow similar paths of development. These presuppositions and conceptions include the projection of modern national states – along with other contrafactual or modern reconstructed entities, such as a medieval ‘Kingdom of Finland’ or neopagan groups – on the past, as well as the so-called world religions paradigm. As part of the contemporary popular cultural medieval imaginary, the game provides a platform for imagining the origins of the present religio-cultural situation, alternative historical developments, and religious and cultural change in general.
The article thinks what kinds of possibilities the game, as part of the contemporary popular cultural medieval imaginary, offers for imagining the origins of present religio-cultural situation, alternative historical developments, and religious and cultural change in general. As such, the game as a cultural product, is discussed in relation to ways of representing cultural and religious differences, world religions paradigm and medievalism.
Medievalism in Finland and Russia: Twentieth- and Twenty-First-Century Aspects